Sedimentological analysis of thin-bedded sequence of Eastern part of West Crocker Formation, Northwest Sabah, Malaysia - Nurul Afifah Mohd Radzir,; Athifah Arshad,; Che Aziz Ali,; Kamal Roslan Mohamed, (Penerbit Universiti Kebangsaan Malaysia, 2023)
It has been suggested that the eastern part of the West Crocker Formation is the slope to the inner fan of a deep-water system. Detailed sedimentological examination of eight outcrops of this formation in this study identified four types of facies: interbedded sandstone and mudstone facies (F1), chaotic facies (F2), and mudstone facies (F3). The immature textures and deformations with rolled-over sandstone block deposits occur as infers due to the presence of an angle of loose sediments, while the repeated thinly bedded sandstones and mudstones were recognized as levee-channel complexes. The overbank was identified as thick mudstone deposits. The sandstone deposits are synonymous with strong energy carried by the head of the turbidity current, while the fine to very fine sediment grains are typical of sediments that are carried by the body and tail of turbidity current and may deposited far away from the first deposition of sand. All the characteristics presence in the environment of slope are to the inner fan of a deep-water system with deformed structures. This deformed slope is believed to be part of a late Eocene accretionary complex formed during the Sabah orogeny.